1992
DOI: 10.1038/ng0792-295
|View full text |Cite
|
Sign up to set email alerts
|

The gene responsible for familial hypocalciuric hypercalcemia maps to chromosome 3q in four unrelated families

Abstract: Familial hypocalciuric hypercalcemia (FHH) is an autosomal dominant syndrome of unknown aetiology characterized by lifelong elevation in serum calcium concentration and low urinary calcium excretion. These features suggest that the causal gene is important for maintenance of extracellular calcium homeostasis by the parathyroid gland and kidney. To identify the chromosomal location of FHH gene(s), we clinically evaluated 114 individuals in four unrelated affected families and performed linkage analyses. The dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(48 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…In 1992, Chou et al showed linkage of the disease gene for FBHH to the long arm of chromosome 3 (27). Subsequently, additional workers confirmed this finding but also demonstrated that a similar phenotype was linked to the short arm of chromosome 19 (28) in one family and to a locus on neither chromosome 3 nor 19 in another (29).…”
Section: Introductionsupporting
confidence: 53%
“…In 1992, Chou et al showed linkage of the disease gene for FBHH to the long arm of chromosome 3 (27). Subsequently, additional workers confirmed this finding but also demonstrated that a similar phenotype was linked to the short arm of chromosome 19 (28) in one family and to a locus on neither chromosome 3 nor 19 in another (29).…”
Section: Introductionsupporting
confidence: 53%
“…In heterozygotes, inactivating CaR mutations cause familial benign hypocalciuric hypercalcemia, and in homozygotes, severe neonatal primary hyperparathyroidism (8,9). In contrast, activating CaR mutations result in autosomal dominant hypocalcemia (10,11).…”
Section: Ntracellular Camentioning
confidence: 99%
“…The CASR was also demonstrated in human insulinoma primary cultures, causing released insulin upon [Ca 2+ o ] stimulation (59), in hepatocytes stimulating bile flow (60) and in antral gastric cells stimulating gastrin secretion (61). (69) and later fluorescence in situ hybridization analysis identified the position of the gene as 3q 13.3-21 (4). Cloning of the CASR was followed by reports of inactivating mutations in this gene in FHH families (70,71).…”
Section: Role Of the Calcium-sensing Receptor In Other Tissuesmentioning
confidence: 99%